Analisis Beban Kerja Pada Operator Mesin Vacum Geiss AG Menggunakan Metode Full Time Equivalent (FTE) Di PT. XYZ - Herry Dwi Prasetyo; Iriani Iriani (Jurnal Kendali Teknik dan Sains, 2024)
Workload analysis provides an opportunity to smooth workload or reduce work activities that do not provide added value. Detailed evaluation and analysis of each work element of a position will display a more detailed workload map. PT. XYZ requires detailed workload mapping to be able to display the load profile for each position. The results of this load mapping can be used for workload normalization analysis. This research uses the Full Time Equivalent (FTE) method. The data used in this research are job descriptions, frequency and working hours. The research results show that the FTE-based workload value of the Vacum Geiss AG operator is FIT (value 1-1.28), namely on 03-10-2023 it is 1.030 and on 04-10-2023 it is 1.030 which is fit because the FTE value is between The value is 1-1.28 so that the operator's work load is appropriate on that day, then on 05-10-2023 on the Geiss AG vacuum machine it is 0.915, it is still underload because the FTE value is below the value of 0.99 so the operator on that day is underloaded. the work is not suitable and additional work is needed.